Finite element analysis and experimental validation of progressive collapse of reinforced rubberized concrete frame. (October 2021) - Alshaikh, Ibrahim M.H.; Bakar, B.H. Abu; Alwesabi, Emad A.H.; Zeyad, Abdullah M.; Magbool, Hassan M.
Abstract: The progressive collapse of reinforced concrete structures usually starts as a local failure, which occurs because of abnormal loads. This can result in enormous economic losses and catastrophic extensive casualties. To avoid high costs of testing full-scale structures and save time, the implementation of the finite element method (FEM) is, therefore, inevitable. This paper aims to develop an FE model using ABAQUS software to simulate the progressive collapse phenomenon of reinforced rubberized concrete frames. The proposed numerical model is validated by comparing the FEM results with the experimental test observations. The numerical study is extended to include more ten models with different stories and details for further understanding of progressive collapse. Based on the results, the simulation model achieved good results compared to the experimental results. Moreover, the numerical models of full-scale frames satisfied the resistance requirements of progressive collapse according to the guidance.